Effectiveness of resistance training in modulating inflammatory biomarkers among Asian patients with sarcopenia: a systematic review and meta-analysis of randomized controlled trials - Xue, Jingxian; Han, Xi; Zheng, Yan; Zhang, Qiuxia; Kong, Lingyu (Frontiers in Immunology, 2024)
Objective: Given the high incidence of sarcopenia among Asians, it is imperative to identify appropriate intervention methods. The International Clinical Practice Guidelines for Sarcopenia, developed by the International Conference on Sarcopenia and Frailty Research (ICFSR) task force, recommends resistance training (RT) as a primary treatment for managing sarcopenia. Inflammatory biomarkers serve as indicators of sarcopenia. However, there is currently insufficient conclusive evidence regarding the effectiveness of RT in modulating inflammatory biomarker levels among Asian participants with sarcopenia.Data sources: Four databases were utilized for this study until October 9, 2023. This study focused on randomized controlled trials (RCTs) that examined the effects of RT on interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), C-reactive protein (CRP), and interleukin-10 (IL-10) about sarcopenia. This study has been registered in the PROSPERO database (CRD42024501855).The meta-analysis included six studies from Asians involving 278 participants. The results showed a significant decrease in RT for IL-6 (weighted mean difference (WMD) = -0.73, 95% confidence interval (CI) = -1.02 to -0.44; n=5). However, no significant differences were found for TNF-α (WMD = -1.00, 95% CI = -2.47 to 0.46; n=5), CRP (WMD = -0.45, 95% CI = -1.14 to 0.23; n=3), and IL-10 (WMD = 0.13, 95% CI = -3.99 to 4.25; n=2). Subgroup analysis revealed that factors including gender selection, intervention methods, frequency, period, and duration could have a particular effect on the part of inflammatory biomarkers.Conclusions: RT has been shown to reduce part of the level of inflammatory markers, specifically IL-6, in Asian sarcopenia participants. However, other inflammatory factors, such as TNF-α, CRP, and IL-10, did not show significant changes. Further research should confirm the impact of RT on these indicators and explore the potential effects of various factors on different inflammatory markers, such as diet, body composition, and medications.